Catchment-scale relief development as the result of long-term agricultural activity, case study on Szekszárd hills, Hungary - Benyhe, Balázs; Kiss, Tímea (Journal of Environmental Geography, 2010)
Human impact has played important role in the relief development of Szekszárd Hills, as the history of viniculture dates back to the Roman Times. Approximately 17 % of the area is used as vineyard. As viniculture is one of the most intensive land-use type and soil erosion is very severe on the loose loessy material of these hills, relief development is quite fast in the area. The aim of the study to estimate the catchmentscale erosional loss of the area caused by viniculture and to evaluate the role of artificial terraces on landscape development. Three smaller catchments were chosen as study areas in the north-east part of the hills. Based on the digital elevation model of the area the minimum net erosion was calculated. The calculations reflect that the amount of erosion was higher (1) on the slopes with southern exposure and (2) in tributary valleys close to the town. The accelerated erosion altered the longitudinal profile of the tributaries and the terraces changed the profile of the intercollin ridges.